PENGARUH MEDIA EDUKASI BOOKLET TENTANG PENCEGAHAN DIARE DAN PNEUMONIA SECARA TERPADU TERHADAP PENGETAHUAN IBU - Hutasoit, Masta; Soenarto, Sri Suparyati; Widiyandana, Widiyandana (Media Ilmu Kesehatan, 2017)
Background: Nearly one-third of child deaths worldwide is due to diarrhea and pneumonia. Every hour, 200 children die because of both diseases. These diseases risk factors are overlapping that children are not given exclusive breastfeeding, do not of handwashing with soap, incomplete immunizations and environmental sanitation factors. Other risk factor is lack of mother’s knowledge in preventing diarrhea and pneumonia. Objective: The aim of this study was to identify the influence of adding booklet media towards to changes in mother’s knowledge on comprehensive diarrhea and pneumonia prevention. Method: This research was a quasi-experimental design research with pretest-posttest nonequivalent control group design. Research subjects were mothers who had toddler aged 0-59 months many as 167 respondents. The sample selection was held randomly with cluster sampling technique. Data collection used questionnaire. Wilcoxon Sign Rank and Mann Whitney Test was performed for bivariate statistics analysis with significance level of 0.05 and confidence level of 95%. Result: There was an increasing knowledge after the health education delivery in both groups. The average enhancement was significantly different in statistics with control group (p=0.001; α=0.05). Conclusion: Health education by utilizing proven education media of booklets on the enhancement of toddler mother related to the comprehensive diarrhea and pneumonia an integrated especially in the aspect of diarrhea.   Keywords: booklets, diarrhea and pneumonia, knowledge.